Congenital hepatic fibrosis in a 9-year-old female patient – a case report - Janowski, Kamil; Goliszek, Maria; Cielecka-Kuszyk, Joanna; Jankowska, Irena; Pawłowska, Joanna (Clinical and Experimental Hepatology, 2017)
Congenital hepatic fibrosis (CHF) is a rare, autosomal recessive disorder, clinically characterized by hepatic fibrosis and portal hypertension. CHF results from ductal plate malformation (DPM) of the intrahepatic bile ducts. Four clinical forms can be observed: portal hypertensive, cholangitic, mixed and latent. CHF is one of the “fibropolycystic diseases” which also include several conditions with a variety of intrahepatic bile duct dilatation and associated periportal fibrosis such as Caroli disease, autosomal recessive and dominant polycystic kidney disease (ARPKD or ADPKD), Ivemark, Jeune, Joubert, Bardet-Biedl, Meckel-Gruber and Arima syndromes. Most of them are accompanied by progressive cystic degeneration of the kidneys. We present the case of a 9-year-old female patient with CHF with nonspecific clinical manifestation and a review of the literature.